Examination of Factors Affecting Youths’ Entrepreneurial Intention: A Cross-Sectional Study - Muhammad Azrin Nazri; Haleemath Aroosha; Nor Asiah Omar (Information Management and Business Review, 2024)
This study aims to examine the predictive effect of enterprise education, perceived social norms, entrepreneurial motivations, perceived structural support and innovativeness on entrepreneurial intention. A total of 150 useable responses were collected among young people living in the capital of Maldives, Male’. A cross-sectional quantitative survey was carried out by using a structured questionnaire. A relevant statistical analytical such as regression analysis was used to test the hypotheses set forth in this study. The descriptive results showed that male respondent is slightly more than female respondent which is consistent with the 2014 census of Maldives showing male population in the country is slightly higher than female. The majority of the respondents participated in this survey are from the age group of 18-22 years old. The main finding of the study showed enterprise education, perceived social norms, entrepreneurial motivations and innovativeness have a positive and significant relationship towards entrepreneurial intention. However, perceived structural support has no significant relationship towards entrepreneurial intention. In this study it was also found that enterprise education was the most significant predictor of entrepreneurial intention followed by entrepreneurial motivation, innovativeness and perceived social norms. This finding makes a considerable contribution to the existing literature on factors influencing entrepreneurial intentions among youth in Maldives. The implication and limitations of the study are also discussed.